PROFIL MASYARAKAT DALAM MEMANFAATKAN AIR BATANG HARI DI KENAGARIAN LUBUK ULANG ALING SELATAN KECAMATAN SANGIR BATANG HARI KABUPATEN SOLOK SELATAN - Wati, Ratna; Edial, Helfia; Zuriyani, Elvi (Pendidikan Geografi, 2013)
This study aims to determine the profile of the community in the use of water in Batang Hari river Kenagarian Lubuk Aling Selatan District Sangir Batang Hari Solok Selatan which include : 1) education , 2 ) economic conditions, 3 ) the level of health dan 4 ) culture.This research is descriptive. The population in this study is people in Kenagarian Lubuk Ulang Aling Selatan having Â± 20 m distance from their homes to the water Batang Hari totaling 302 households, each household can be represented by one households. Respondent sample taken with the technique of random sampling proportional to the proportion of 25 % so that the sample was 76 families .The research found that : 1 ) the condition of the education level of the people who use water Batang Hari generally never get a formal education with education level taken is not complete primary school - The End SD , although so many are out of school . Considers very important the public education so that the children need to get an education . Currently children who are still studying are generally 1 and there are children who drop out of school , ( 2 ) the economic condition that utilizes water generally is Batang Hari gold miners with income > Rp 5.000.000/bulan . Society also has a side job as a farmer with revenue generally Rp 1,000,000 - Rp 2.000.000/bulan . Society also has a family member that works but needs less fulfilled life , ( 3 ) the condition of public health that utilizes water generally has Batang Hari WC / private bathroom but rarely used . Clean water sources are rivers , water treatment generally boiled water consumed while health is generally decent and ( 4 ) cultural communities like bathing in the river for reasons more to socialize with the people around